Assessment Knowledge of Parents Regarding Health Preventive Measures and Self-Care of Hemophilia Children - Hussein Ali Damad, Wisam Mishaan Muttaleb, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Together hemophilia A and B are categorized through spontaneous indoors bleeding and excessive bleeding later on accidents or surgery. The biggest common places for bleeding are into joints and much less commonly in muscle tissues and organs such as the talent or kidneys. Objective(s): The aim of the study is to assess knowledge of parents regarding health preventive measures and self-care of hemophilia children. Method: a descriptive design is carried out through the use of questionnaire format for non –probability (purposive) sample of (40) patients who their children have hemophilia and treat in Blood Disease center in - AL_ Nasiriya City. Results: the study result showed that the highest rate of parents who participate in the study were father in age 38 years and more, who graduated from institute and their social status was married. The study show that the majority of participants have low information about self-care and health preventive measures for their children with hemophilia. Conclusion: The study participants have a low knowledge level about health preventive measures and self-care and health preventive measures of hemophilia children. Recommendations: Preparing lectures and providing simple manual booklet prepared and presented to health care providers and parents with hemophilia to enhancing their homecare (illness, diet, fluid, medication exercise and treatment) of patients.